Comorbidity of Pain and Depression in a Lumbar Disc Herniation Model: Biochemical Alterations and the Effects of Fluoxetine - Cai, Lun; He, Qianchao; Lu, Yongjing; Hu, Yuying; Chen, Wei; Wei, Liping; Hu, Yueqiang (Frontiers in Neurology, 2019)
Summary of Background Data: Depression is one of the most common comorbidities in patients with chronic low back pain. However, the mechanisms of depression in chronic low back pain patients and the effect of antidepressants on the comorbidity of pain and depression need to be further explored. The establishment of the appropriate animal models and of more effective therapies is critical for this comorbidity. Lumbar disc herniation (LDH) is the most common disease that causes low back pain. The current study examined whether an LDH model shows behavioral and biochemical alterations that are in accordance with the characteristics of the comorbidity of pain and depression and tested the effect of fluoxetine (FLX) on these measures. Objective: The current study examined whether an LDH model showed the behavioral and biochemical alterations that were in accordance with the characteristics of the comorbidity of pain and depression and tested the effect of FLX on these measures. Methods: The LDH animal model was generated by the implantation of the autologous nucleus pulposus on the left L5 nerve root just proximal to the dorsal root ganglion in Wistar rats. Pain intensity was evaluated by mechanical allodynia and thermal hyperalgesia, and changes in depressive behavior were examined by the taste preference and forced swim tests. Hippocampal serotonin (5-HT) levels were measured by liquid chromatography-mass spectrometry, and tumor necrosis factor-α (TNF-α) mRNA was quantified using real-time reverse transcriptase PCR. Results: LDH resulted in chronic pain, which further induced depressive behavior that persisted for 6 weeks after surgery. There were decreased 5-HT concentrations and upregulated TNF-α mRNA levels that were accompanied by behavioral changes. FLX treatment improved depressive behavior and moderately alleviated pain through increased 5-HT concentrations, and inhibited TNF-α mRNA expression. Conclusions: In summary, our studies provide initial evidence that the LDH chronic pain model might serve as a model of the comorbidity of low back pain and depression. The finding that FLX improved depressive behavior and pain through normalized 5-HT concentrations and TNF-α mRNA expression establishes the initial mechanism of the comorbidity of pain and depression.